2003
DOI: 10.1177/0733464803254010
|View full text |Cite
|
Sign up to set email alerts
|

The Delivery of Health Care to the Elderly: Lessons Learned from the Creation of Interorganizational Linkages Between Area Agencies on Aging and Managed Care Organizations

Abstract: This process evaluation of the development of strategic alliances between area agencies on aging (AAAs) and managed care organizations (MCOs) identified factors that facilitated the establishment of these partnerships along with the challenges they faced. Data were gathered from two Pennsylvania sites (Philadelphia and Erie), using documentation and records along with interview data that were gathered during site visits. The principal findings include: (a) The AAAs experienced difficulty in "selling" their ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The TAPN Membership Survey Form (questionnaire) was developed by the researchers who reviewed the by-laws; mission, goals, and objectives; minutes of meetings; other documents of TAPN; and the literature regarding networks (Hebert & Veil, 2004;Hill, 2002;Gajda, 2004;Iutcovich & Pratt, 2003). The initial form was reviewed by the Board of TAPN, the director of TAPN, and selected TAPN members.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The TAPN Membership Survey Form (questionnaire) was developed by the researchers who reviewed the by-laws; mission, goals, and objectives; minutes of meetings; other documents of TAPN; and the literature regarding networks (Hebert & Veil, 2004;Hill, 2002;Gajda, 2004;Iutcovich & Pratt, 2003). The initial form was reviewed by the Board of TAPN, the director of TAPN, and selected TAPN members.…”
Section: Instrumentationmentioning
confidence: 99%
“…There, however, were no differences in the utilization of services between the groups (Tourigny et al, 2004). Finally, in a study in Pennsylvania, strategic alliances between area agencies on aging (AAAs) and managed care organizations (MCOs) were examined (Iutcovich & Pratt, 2003). Here, it was found that there was confusion regarding which organizations should provide specific services, the MCOs did not fully accept the services the AAAs were selling, and there appeared to be little concern regarding consumer outcomes.…”
mentioning
confidence: 99%